Monetary policy, a market price approach - Johnson, Manuel H.; Keleher, Robert E. (Westport, Conn. : Quorum Books, 1996)
This book presents an alternative market price approach to monetary policy, in addition to how monetary policy makers can use market prices to produce price stability.
Includes bibliographical references and index.
nmn, 26/07/2016
Loans
Keywords: Monetary policy; Market price; United states